Deep in the Jelly: Histochemical and Functional Aspects of Mucilage-Secreting Floral Colleters in the Orchids Elleanthus brasiliensis and E. crinipes - Cassola, Fábio; Nunes, Carlos Eduardo Pereira; Lusa, Makeli Garibotti; Garcia, Vera Lúcia; Mayer, Juliana Lischka Sampaio (Frontiers in Plant Science, 2019)
Colleters are trichomes or emergencies that produce a sticky exudate consisting of a mixture of mucilage, lipids, terpenes, and phenolic compounds. Colleters occur in at least 60 families of angiosperms; however, reports of them are scarce for the Orchidaceae. Elleanthus brasiliensis is distinguished by the presence of an abundant gelatinous secretion that covers almost all of its inflorescences. We aimed to describe the histology of colleters in inflorescences of E. brasiliensis and E. crinipes, and to analyze the chemical composition of their secretion to better understand the functions of these secretory structures. Due to the low frequency of colleters and lack of visible secretion in E. crinipes, histochemical tests and chemical analyses were not performed for this species. Colleters and their secretion are hydrophilic and lipophilic. The GC-MS analysis confirmed the presence of γ-sitosterol and palmitic, linoleic, and stearic acids in the secretion of E. brasiliensis. Histochemical tests further revealed the presence of pectin, mucilage, lipids, terpenes, phenolic compounds, and proteins. Infrared analysis indicated the possible presence of polysaccharides in the secretion. The occurrence of colleters in both species studied and in other orchids described in the literature suggests that these structures are common in the inflorescences of tropical orchids. In these environments, the hydrated polysaccharides in the secretion form a dense matrix that can act as a physical barrier, and terpenes may help to protect against herbivores and pathogenic microorganisms. This information broadens our knowledge of the morphological and chemical diversity of the secretions produced by orchid colleters.